Magnetic resonance phase contrast velocity mapping for flow quantification in irregular heart rhythms using radial k-space ultrashort echo time imaging - Hell, MM; Francis, JM; d'Arcy, J; Robson, MD; Neubauer, S; Achenbach, S; Myerson, SG (Elsevier, 2020)
Background Phase contrast velocity mapping sequences utilising ultrashort echo time (UTE) radial k-space sequences have been used to reduce intravoxel dephasing at high velocities. We evaluated the accuracy of the UTE flow sequence for mitral regurgitation (MR) quantification, including patients with atrial fibrillation.